Lean and/or Six Sigma for process optimization in the perioperative period: an integrative review. - Gardim, Lucas; Rodrigues dos Santos, Fernanda; Moreno Dias, Bruna; El Hetti Fuentes, Lívia Barrionuevo; Pereira Silveira, Renata Cristina de Campos (Revista Brasileira de Enfermagem, 2024)
Objective: To analyze the evidence on the influence of Lean and/or Six Sigma for process optimization in the perioperative period. Methods: Integrative review carried out in the MEDLINE (PubMed), Web of Science, EMBASE, CINAHL, Scopus and LILACS databases on the use of Lean and/or Six Sigma to optimize perioperative processes. The studies included were analyzed in three thematic categories: flow of surgical patients, work process and length of stay. Results: The final sample consisted of ten studies, which covered all operative periods. Lean and/or Six Sigma make a significant contribution to optimizing perioperative processes. Final considerations: Lean and/or Six Sigma optimize perioperative processes to maximize the achievement of system stability indicators, making it possible to identify potential problems in order to recognize them and propose solutions that can enable the institution of patient-centered care.